Beyond the on-line library - the Learning Environment - Bob Banks (Information Research: An International Electronic Journal)
This paper describes a collaborative project which has defined requirements and a model for holistic networked learner support. Based on these requirements, a working prototype for a Learning Environment has been developed. Technical, organisational and business issues which have arisen are discussed.